IMPLEMENTASI AMSAL 17:22 DI MASA PANDEMI COVID-19 SEBAGAI SATU CARA UNTUK MENAIKAN IMUN TUBUH - Nubatonis, Thimotius; Hendriks, Alvyn Cesarianto; Hutagalung, Stimson; Ferinia, Rolyana (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
During a pandemic, the body's immune system is vital because it is the body's immune system that plays a role in fighting viruses and helping the body recover. The heart and mind are very influential on the body's immune system. Proverbs 17:22 records that the human heart and mind are persuasive. Based on this background, the purpose of this paper is to prove the truth of Proverbs 17:22 about a happy heart as a scientifically proven medicine that can affect the body's immune system. Then, Proverbs 17:22 can be implemented during the Covid-19 pandemic. The method used in this study is a qualitative method whose results are explained narratively with data collection techniques through literature study. The biblical text used as the basis will be interpreted using the hermeneutic approach. The results obtained from this study are that the text of Proverbs 17:22 can be scientifically proven. A happy heart and a good state of mind will increase the body's immune system to become the body's natural medicine. Vice versa, a heart filled with sadness and stress will trigger a weakening of the immune system to be vulnerable to disease. Thus the text of Proverbs 17:22 can be implemented or applied during the current Covid-19 pandemic.